Diffuse alveolar hemorrhage with nivolumab monotherapy - Vickie R. Shannon; Sumit K. Subudhi; Lei Huo; Saadia A. Faiz (Respiratory Medicine Case Reports, 2020)
We describe a 60 year old man who developed respiratory insufficiency after treatment with 2 rounds of nivolumab monotherapy. Imaging revealed subtle ground glass infiltrates which progressed to diffuse opacities and consolidation. The patient was treated with high dose corticosteroids, empiric antimicrobial therapy and infliximab. Bronchoscopy with lavage revealed negative cultures and progressive bloody aliquots of fluid consistent with diffuse alveolar hemorrhage. The patient succumbed to respiratory failure. An autopsy study confirmed extensive alveolar hemorrhage. Our reports highlights clinical and diagnostic findings with immunotherapy-induced pneumonitis.